Terminal Insomnia as a Phenotypic Biomarker of Geriatric Depression in a Balinese Cohort: A Cross-Sectional Analysis of Circadian Disruption and Sleep Continuity - Made Citra Riesti Wulan; Wayan Saka Rahayu; Wayan Wiradana (Phlox Institute: Indonesian Medical Research Organization, 2026)
Introduction: Sleep architecture undergoes significant fragmentation during aging, yet the specific phenotypic expression of insomnia in the context of geriatric depression remains under-characterized. While the bidirectional relationship between depression and sleep is established, few studies distinguish between initial, middle, and terminal insomnia subtypes in Southeast Asian geriatric populations. This study aims to characterize the predominant insomnia phenotypes among elderly patients with depression and investigate the association between sociodemographic determinants, chronic morbidity, and specific sleep continuity disturbances. Methods: A cross-sectional analytical study was conducted at the Geriatric Outpatient Clinic of Karangasem Regional General Hospital, Bali, Indonesia (N=58). Psychometric evaluation utilized the Geriatric Depression Scale (GDS-15) to screen for depressive symptoms and the Pittsburgh Sleep Quality Index (PSQI) to assess global sleep quality. Insomnia phenotypes were clinically adjudicated based on diagnostic interviews. To account for potential confounders, body mass index (BMI) and chronic pain scores were included in the analysis. Data were analyzed using Firth’s Penalized Likelihood Logistic Regression to stabilize estimates given the sample size. Results: The prevalence of depression in the cohort was 58.3%. Among depressed elderly patients, terminal (Late) Insomnia was the predominant phenotype, affecting 76.0% of the subgroup, followed by middle insomnia (66.7%) and initial insomnia (36.4%). Multivariate analysis adjusted for age, chronic disease status, BMI, and pain demonstrated that Terminal Insomnia was the strongest independent predictor of depression (Adjusted OR 6.42; 95% CI 2.15–14.8; p<0.001). Conclusion: Terminal insomnia represents a distinct and dominant clinical phenotype of depression in this geriatric cohort, potentially reflecting underlying circadian phase advances and HPA-axis hyperactivity characteristic of melancholic depression. Clinicians should prioritize sleep maintenance strategies over sleep induction pharmacotherapy in this population.